Pemanfaatan Website untuk Promosi Pariwisata di Kawasan Agrowisata Puncak Labuang - Kurnia, Rahmi Putri; Defni; Hadi, Ronal; Wijaya, Taruma Leo; Fryonanda, Harfebi; Hafizun, Altaf (AJAD : Jurnal Pengabdian kepada Masyarakat, 2024)
The development of technology-based tourism is a strategic step to increase the competitiveness of local destinations, such as Puncak Labuang in Nagari Limau Manis. This community service activity aims to increase the visibility and accessibility of Puncak Labuang tourism information by developing the visit.limaumanis.id website. The methods used include identifying needs, designing, developing systems, testing functionality, and training representatives of the Limau Manis Community Empowerment Forum (FPM). The activity results show that users consider this website easy to use and valuable. The training provided improves the ability of FPM representatives to manage and update content independently. A post-training survey revealed that 90% of participants felt more confident operating the website, and 88% considered the interface easy to understand. This implementation is expected to support the promotion of local tourism effectively and sustainably, which positively impacts the economy and welfare of the local community. This program shows the importance of synergy between technology and society for developing local potential.